Food safety knowledge, attitudes and practices among food handlers in Chiang Mai Province, Thailand - Jenpanich, C.; Unger, Fred; Alter, T.; Chaisowwong, W. (Chiang Mai University, 2016)
Foodborne illness have a great impact on public health worldwide. In Thailand, most foodborne illnesses are attributed to cross contamination in food especially from animal origin and drinking water. There is a high production and domestic consumption of pork. Food handlers play an important role to reduce contamination of microbial hazards along the food chain. Good personal hygiene is an essential part for food safety. The objectives of this study were to assess the level of knowledge, attitudes and practices (KAP) of food handlers and to assess the level of microbiological hygiene indicators at slaughterhouses and markets. A cross-sectional study was conducted in 16 slaughterhouses and 31 markets in Chiang Mai province, Thailand during December 2014 to May 2015. A total of 32 slaughterhouse workers and 51 pork sellers were evaluated by KAP using questionnaires combining likert scales. Two focus group discussions were performed in slaughterhouse workers and in-depth interviews were assessed for animal health and public health authorities, markets and slaughterhouse managers, and consumers regarding food hygiene and food safety issues. The result from questionnaires showed that most of the food handlers had high scores of knowledge regarding personal hygiene and cross contamination related to food safety while they showed low scores in knowledge in aspects of foodborne illnesses. This result is in accordance with the result from the focus group discussions. Some findings hint to an inconsistency between attitudes and practices; for example, food handlers agreed that protective equipment can reduce cross contamination, but they practically did not wear masks because they felt uncomfortable especially in summer and some consumers may relate this to a health problem of the food sellers. The qualitative data indicated that some good hygiene measures are inappropriate in the context of their practical implementation and some of these hygiene practices are not in accordance with their socio-economic status; for example, food handlers came to work even they got sick because if they did not work, they did not get money for supporting in their lives.